Islamic Character Education Strategies at Pesantren Manbaul Hikam: Integrative Cultural-Spiritual Model - Musadad, Ahmad; Nahidloh, Shofiyun; Nasik, Khoirun; Choiri, Muttaqin; Pujiati , Tri; Asmoi, Asmoi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Islamic character education is a fundamental pillar in shaping a morally upright generation amid the challenges of value globalization. This study aims to examine the strategies for instilling Islamic character values implemented at Pesantren Manbaul Hikam, Bangkalan, Madura. The main focus of this research is to identify the approaches and educational methods used by pesantren to embed Islamic character values for students (santri). This study employed a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, participant observation, and documentation. The findings reveal that the strategies for Islamic character education at Pesantren Manbaul Hikam are carried out through the integration of exemplary behavior (uswah hasanah), habitual Islamic practices in daily life, and classical Islamic text learning (kitab kuning) which emphasizes moral teachings. Moreover, the conducive boarding school environment and the close relationship between the kiai (Islamic teacher) and the students enhance the internalization of core character values such as honesty, responsibility, simplicity, and obedience. In conclusion, Islamic character education at Pesantren Manbaul Hikam is not merely cognitive or affective, but also practical through a consistently cultivated culture of daily life. This strategy demonstrates that traditional pesantren can serve as a relevant and adaptive model for Islamic character education in the face of modern societal dynamics.